2015
DOI: 10.1002/sec.1265
|View full text |Cite
|
Sign up to set email alerts
|

A changeable personal identification number‐based keystroke dynamics authentication system on smart phones

Abstract: One can apply cell phones to access e-bank, buy stocks, pay credit card bills, and so on. The security issues of cell phones become extremely important. Most of subscribers use personal identification number (PIN) codes which combined with 6-8 numbers to protect their subscriber identity module cards from illegal accesses. It is easily to be decoded by the dictionary attack or shoulder surfing attack. Many studies employed keystroke dynamics to protect the PIN code, and the relative results exhibit that keystr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Surprisingly, for one of the 8-digit PIN ("12598416"), the EER value was 4.45%, marginally worse than the 4-digit PIN ("3244"). This finding is in contrary to previous studies (Chang et al 2015;Praher and Sonntag 2016;Shen et al 2016) which have suggested that longer input strings produce a better accuracy performance.…”
Section: Related Workcontrasting
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, for one of the 8-digit PIN ("12598416"), the EER value was 4.45%, marginally worse than the 4-digit PIN ("3244"). This finding is in contrary to previous studies (Chang et al 2015;Praher and Sonntag 2016;Shen et al 2016) which have suggested that longer input strings produce a better accuracy performance.…”
Section: Related Workcontrasting
confidence: 99%
“…The work reported in (Chang et al 2015) was somewhat unique. The authors proposed a method to allow subjects to change their PINs without rebuilding the authentication model.…”
Section: Related Workmentioning
confidence: 97%
“…The work reported in (Chang et al, 2015) was rather unique. The author proposed a method to allow subjects to change their PINs without rebuilding the classification model.…”
Section: Performance Investigationmentioning
confidence: 96%
“…The work reported in [6] was somewhat unique. The authors proposed a method to allow subjects to change their PINs without rebuilding the authentication model.…”
Section: Related Workmentioning
confidence: 98%